2001
DOI: 10.1152/jn.2001.86.5.2374
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure of Testosterone Prevents SDN-POA Neurons of Postnatal Male Rats From Apoptosis Through NMDA Receptor

Abstract: The role of N-methyl-D-aspartate (NMDA) receptor in mediating the effect of testosterone exposure prenatally on neuronal apoptosis in the sexual dimorphic nucleus of the preoptic area (SDN-POA) of rats was studied. The endogenous testosterone was diminished by prenatal stress (PNS) or simulated by testosterone exposure (TE) to understand the effect of testosterone on NR(1) (a functional subunit protein of NMDA receptor) expression and neuronal apoptosis. To further study whether the testosterone, after being c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…Previously, we have demonstrated that the apoptotic incidence of neurons in SDN-POA of male rats is significantly increased when NMDA receptor is blocked by MK-801 (Hsu et al 2001) and the physiological activation of NMDA receptor may protect against neuronal death by transcriptional increase of some survival-related genes, including COII, in SDN-POA during sexual development (Hsu et al 2005). In this study, we attempted to map the signaling pathway of NMDA receptor-mediated neuronal survival in the GT1-7 cell lines, which were derived from hypothalamic GnRH neurons and expressed NMDA receptor as well as mitochondrial COII genes, by comparing the time course of intracellular events, which have been suggested to be involved in the neuronal apoptosis, induced by blocking the activation of NMDA receptor.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Previously, we have demonstrated that the apoptotic incidence of neurons in SDN-POA of male rats is significantly increased when NMDA receptor is blocked by MK-801 (Hsu et al 2001) and the physiological activation of NMDA receptor may protect against neuronal death by transcriptional increase of some survival-related genes, including COII, in SDN-POA during sexual development (Hsu et al 2005). In this study, we attempted to map the signaling pathway of NMDA receptor-mediated neuronal survival in the GT1-7 cell lines, which were derived from hypothalamic GnRH neurons and expressed NMDA receptor as well as mitochondrial COII genes, by comparing the time course of intracellular events, which have been suggested to be involved in the neuronal apoptosis, induced by blocking the activation of NMDA receptor.…”
Section: Discussionmentioning
confidence: 97%
“…5 mmol/l spermidine and 1 mmol/l dNTPs at 42 8C for 60 min (Hsu et al 2001). PCR was performed with specific primers for COII, PGC-1, mtTFA, glyceraldehydes-3-phosphate dehydrogenase (GAPDH) and 18S.…”
Section: Semi-quantitative Reverse Transcription-pcr (Rt-pcr) Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the low apoptotic incidence in the SDN-POA in male rats may contribute to its large volume compared to that in female rats. Our recent report provided evidence that estradiol converted from testosterone might prevent apoptosis in the SDN-POA neurons of male rats by enhancing expression of the N-methyl-D-aspartate (NMDA) receptor (Hsu et al 2001). However, the molecular mechanism by which activation of NMDA receptor mediates the fate of neurons remains unclear.…”
Section: Introductionmentioning
confidence: 99%